Assessment of Child Complications Related to Fluids and Electrolyte Disorders in Babel Hospital for Mothers and Children in AL-Hilla City (Medico Legal Update, 2020)
This is a descriptive study aimed at assessing children’s complications related to fluid and electrolytedisorders. Data were collected in Babel Hospital for Maternal Children through a questionnaire model anddata analysis by frequency and percentage, the results showed that (86%) of children lose their appetite,while (14%) They do not lose their appetite, results also show (72%) suffer from diarrhea, while (28%) donot suffer from diarrhea, as results show (20%) suffer from dry mouth, while (80%) do not suffer from drymouth, The results also show (10%) suffer from syncope, (90%) do not suffer from syncope.Objectives: Evaluation of complications related to fluid disturbances with electricity in the child.Knowing the demographic characteristics of young children who suffer from fluids in disorders such as age,number of children in the family, and number of children in the family.Methodology: A descriptive study used to assess complications related to a fluid electrolyte disorder fora young child. This study was conducted at Baby and Mother Hospital of Babel during the period (5/2 /2019_3 / 6/2019).A purposeful sample of (50) children, and the study was proven by a committee in the College of Nursing.Statistical SPSS was used to analyze the results of this studyResults: According to the interpretation and discussion of the study results, (72%) of the children haddiarrhea (48%) of the children had vomiting. (62%) are dependent on artificial feeding, (34%) of childrenhave experienced accidents or fall from a height.